The use of epidemiological measures to estimate the impact of primary prevention interventions on CHD, stroke and cancer outcomes: Experiences from Herefordshire, UK - Ahmed M. Syed; Alison Talbot-Smith; Isla Gemmell (Springer, 2019)
Background: CHD, stroke and cancers are the major causes of mortality in the UK and are responsible for significant amounts of morbidity and healthcare costs. This study examines the proportion of CHD, stroke and cancer owing to specific risk factors in Herefordshire, UK. It estimates the population impact of a number of interventions being implemented to reduce these risk factors, through the NHS Health Check program and the Herefordshire Health Improvement Plan. The present study also aims to demonstrate the value of epidemiological measures in providing evidence-based public health information in policy-making to aid decision makers when prioritizing investments and optimal use of resources. Methods: The epidemiological measures-'Population Attributable Risk' and 'Population Impact Measures'-were used to assess the impact of interventions to reduce the burden of CHD, stroke and cancer. Results: Implementation of the NHS Health Check program will prevent 63 CHD events, 90 MI events and 125 stroke events, and one lung cancer over a period of 5 years. Reducing specific risk factors by 5% annually through the Health Improvement Plan will prevent 65 CHD events, 25 MI events, 140 stroke events, four lung cancer, one breast cancer and four colorectal cancer cases in Herefordshire if targets are met over a period of 5 years. Conclusion: Physical inactivity and obesity are the major causes of CHD and stroke events (incidence and mortality) in Herefordshire. Their impact is greater than the combined effect of hypercholesterolemia and hypertension. Epidemiological measures used in this study proved to be excellent tools in providing evidence-based public health information. Their use is strongly recommended to support prioritization of primary prevention interventions.